2009
DOI: 10.1021/jp809171f
|View full text |Cite
|
Sign up to set email alerts
|

Non-Injection and Low-Temperature Approach to Colloidal Photoluminescent PbS Nanocrystals with Narrow Bandwidth

Abstract: Colloidal photoluminescent (PL) PbS nanocrystals have attracted a lot of attention in various applications such as bioimaging and optical telecommunications due to their tunable bandgap in the near-infrared region of the electromagnetic spectrum. Hot-injection processes seem to be the best to engineer high-quality PbS nanocrystals. However, there is a limited body of literature documented on the syntheses, with little information on synthetic parameters affecting the optical properties of the product. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
93
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 50 publications
4
93
1
1
Order By: Relevance
“…The contribution of the injection to particle nucleation seems minor, and it is shown that injection can be replaced entirely by an accurately controlled heating up of the solution containing all reagents (including the cobalt precursor) from room temperature to the nucleation temperature. This synthetic method, which is often termed either "non-injection synthesis" [15,16] or "heating-up synthesis", [3,11] results in nanoparticles that are nearly identical to those made by the hot-injection method.We synthesized cobalt nanoparticles by injecting dicobalt octacarbonyl, [Co 2 (CO) 8 ], dissolved in a small amount of ortho-dichlorobenzene (o-DCB, b.p. 181 8C) into a solution of oleic acid and trioctylphosphine oxide (TOPO) in o-DCB at reflux.…”
mentioning
confidence: 99%
“…The contribution of the injection to particle nucleation seems minor, and it is shown that injection can be replaced entirely by an accurately controlled heating up of the solution containing all reagents (including the cobalt precursor) from room temperature to the nucleation temperature. This synthetic method, which is often termed either "non-injection synthesis" [15,16] or "heating-up synthesis", [3,11] results in nanoparticles that are nearly identical to those made by the hot-injection method.We synthesized cobalt nanoparticles by injecting dicobalt octacarbonyl, [Co 2 (CO) 8 ], dissolved in a small amount of ortho-dichlorobenzene (o-DCB, b.p. 181 8C) into a solution of oleic acid and trioctylphosphine oxide (TOPO) in o-DCB at reflux.…”
mentioning
confidence: 99%
“…[19,[24][25][26] Very recently, the group of Yu developed a new non-injection approach to synthesize NIR-emitting PbS QDs in ODE. [27] These results represented the best optical quality of the NIR fluorescent PbS QDs in organic media. However, unfortunately, these methods are still complicated and involve the dangerous chemical bis(trimethylsilyl) sulfide [(TMS) 2 S] or poorly reactive elemental S.…”
Section: Introductionmentioning
confidence: 79%
“…[19,[21][22][23][24][25][26][27] As expected, if we can combine the respective advantages of both approaches properly, for instance, to synthesize oil-soluble QDs by using water-soluble anion precursors, the synthesis steps of the traditional organic-phase methods will be simplified greatly. However, this has proved to be a difficulty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Furthermore, the role of DPP in eq 1 approach was not discussed and the DPP amount was not explored.…”
Section: ' Introductionmentioning
confidence: 99%